Korrektur stationsabhängiger Fehler bei GNSS - Knöpfler, Andreas (Schriftenreihe des Studiengangs Geodäsie und Geoinformatik / Karlsruher Institut für Technologie, Studiengang Geodäsie und Geoinformatik, 2015)
GNSS based positioning techniques have become a standard tool in geodesy. Despite important developments both in receiver and processing technology, site dependent errors, like multipath effects or residual errors in the calibration values of the receiving GNSS antenna, are still a major error source in highly precise GNSS positioning. The method used in this work is based on stacking of observation residuals and therefore able to reduce these error sources effectively.